National Framework for Climate Services - Ethiopia: Coordination Guideline - National Meteorological Agency (National Meteorological Agency, 2021)
Whereas main economic sectors and livelihoods in Ethiopia are increasingly becoming vulnerable to risks associated with extremes of weather and climate. Whereas national and international commitments to address the impacts of climate extremes are in place and provide the enabling environment for national resilience building efforts. Whereas building resilience of known economic sectors and livelihoods in Ethiopia requires transforming international and national commitments into practical action, collaboration and ensuring availability, access, and application of timely, reliable and fine resolution climate services. Whereas collaborative efforts of climate service institutions in Ethiopia since early 2018 resulted in the launching of the National Framework for Climate Services (NFCS) comprising the strategic plan and costed action plan. Whereas the NFCS strategic plan has ambitious aims of delivering reliable climate services customized to different groups of users and building the capacity of climate institutions thereby contributing to effectiveness of the climate resilient green economy (CRGE) strategy and other overarching development plans of the nation. Whereas the NFCS entails delivery of climate services in key climate sectors encompassing water and energy, agriculture, health, disaster risk management, and environmental protection. Whereas delivery of effective and sustained climate services in key climate sensitive sectors entails coordinated actions involving different climate institutions engaged in various sectors and having wealth of experiences and expertise. Whereas joint implementation of the NFCS requires a coordination guideline that provides clear direction on institutional arrangements, sets of principles and procedures, responsibilities, and accountability mechanisms that enable climate institutions to work towards a common end.